PENGARUH SHOPPING LIFESTYLE DAN STORE ATMOSPHERE TERHADAP IMPULSE BUYING (Survei Pada Konsumen Toko Mayola Shop Mega Mall Kota Bengkulu) - Saputri, Novtari Widia; Kusuma, Merta (Yayasan Insani Mandiri Santani, 2020)
The Mayola was firstly opened in November 2018. This shop is one of the stores at mega mall in Bengkulu city. It sells women's fashion products. This study aims to determine how much effect of the Shopping Lifestyle and Store Atmosphere on the Impulse Buying on consumers of Mayola Shop Mega Mall Bengkulu City. The method used in this research was quantitative data analysis. The population were consumers at Mayola Shop totaling 120 people. To determine thesampling, the researcher used accidental sampling method. The data wasÂ collected using a questionnaire. There are several data analysis techniques used in this study, including instrument test, classic assumption test, respondent response analysis, multiple linear regression analysis, coefficient of determination, and also hypothesis testing. Based on the results of multiple linear regression, the regression equation form Y = 3.099 + 0.333 (X1) + 0.122 (X2). The Results and hypotheses show that Shopping Lifestyle (sig <Î± = 0.001 <0.050), Store Atmosphere (sig <Î± = 0,000 <0.050), simultaneously have a significant effect on Impulse Buying. Partially both the Shopping Lifestyle and Store Atmosphere variables have significant effect on Impulse Buying.Â Keywords: Shopping Lifestyle, Store Atmosphere, Impulse Buying